Facades : design, construction & technology - Menzel, Lara, 1978- (Berlin : Braun, 2012)
The facade is the visible surface of the building shell. It separates the interior from the exterior, form from function, users from passers-by. In addition to functional demands, the surrounding urban space and aesthetic appeal, sustainability parameters are gaining in importance in this day and age. For this reason, facade design, construction and technology receive ever-increasing attention in the building industry today. This volume provides an overview of the extensive range of possibilities, featuring the great creative and technical variety of today's facades. The presentation focuses on revealing photos, technical specifications, and detailed drawings. The projects from around the world vividly exemplify how the relationship between the interior and exterior is defined, designed and implemented in each individual case.
Includes index.
ARC
Keywords: Facades -- Design and construction; Facades -- Designs and plans; Architectural design